1992
DOI: 10.1061/(asce)0733-9437(1992)118:5(776)
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Roughness Coefficients for Native Rangelands

Abstract: A subfactor-based regression technique for estimating hydraulic roughness coefficients for shallow overland flow was developed from simulated rainfall/runoff plots originallycollected for erosion studies. The data were collected from 14 different native rangeland areas in the western United States. Rainfall was appliedat a constantintensity of 65mm/hrfrom a rotating-boom rainfall simulator. Surfaces evaluated ranged from smooth bare soil to gravelly bare soil and sparsely to densely vegetated rangeland areas. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
3
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 17 publications
0
57
3
1
Order By: Relevance
“…These plots carried some surface stones and a 10-40 per cent vegetation cover. Weltz et al (1992) derived a relation for the component of f attributable to organic litter, treated separately from soil grain or stone cover roughness:…”
Section: Comparing the Estimates Of F With Published Resultsmentioning
confidence: 99%
“…These plots carried some surface stones and a 10-40 per cent vegetation cover. Weltz et al (1992) derived a relation for the component of f attributable to organic litter, treated separately from soil grain or stone cover roughness:…”
Section: Comparing the Estimates Of F With Published Resultsmentioning
confidence: 99%
“…Thus, Abrahams and Parsons (1990) indicate that, when the zero depths are not included, the corrected value of h hill ranges from 0·00424 to 0·00709 m, and therefore h hill = 0·005 m was used for these calculations. Hillslope friction is typically 0·50 m −1/3 s for woody brush, litter and duff, or shrubland and grassland (Weltz et al 1992;NRCS, 1986). Critical shear stresses measured for agricultural soils range from about 0·8 to 6·5 N m −2 (Elliot et al, 1989), and Dietrich et al (1992) reported values that range from 20 to 100 N m −2 for saturated overland flow on grasslands.…”
Section: Sensitivity Of the Critical Area To Wildfirementioning
confidence: 99%
“…Fires decrease the hillslope friction by removing obstructions, which reduces the friction to values typical of bare soil (n hill = 0·01 m −1/3 s; Weltz et al, 1992;NRCS, 1986). A consequence of removing these obstructions is that the time for runoff to reach the channel decreases.…”
Section: Sensitivity Of the Critical Area To Wildfirementioning
confidence: 99%
“…Various attempts have been made to predict f, from data on soil cover, stoniness and flow Reynolds number using regression analysis (e.g. Gilley et al, , 1992Weltz et al, 1992;Abrahams et al, 1994). Extrapolation of these equations to surfaces other than those they were developed for is questionable, considering their empirical nature and the fact that different factors may control hydraulic roughness on different surfaces.…”
mentioning
confidence: 99%